2018
DOI: 10.1016/j.clml.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mutations in B-Acute Lymphoblastic Leukemia Among African American and European American Children

Abstract: Our study revealed aberrant genetic aberrations in signaling networks that may contribute to race-specific aspects of leukemogenesis. Our results suggest the value of WES as a tool for development of individual gene signatures and gene scores for AA and EA children afflicted by B-ALL. These findings may ultimately impact disease management and contribute to the elimination of disparate outcomes in AA children with B-ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…For example, Chow et al (2010) discussed that although Black children have a 28% decreased risk for ALL (odds ratio = 0.72; confidence interval [0.65, 0.80]) compared with White and Hispanic children, there may be genetic (tumor and germline DNA) as well as environmental factors that increase their susceptibility to cancer. In addition, in epidemiologic studies of children with leukemia, unfavorable disease-specific characteristics were observed more in diverse racial/ethnic groups compared with White, non-Hispanics children (Aldrich et al, 2006;Njoku et al, 2013) and these unfavorable characteristics in the biology of the leukemia and/or genetic aberrations may contribute to disparities in OS for children with ALL (Linabery & Ross, 2008;Lohmueller et al, 2008;Reddy et al, 2018). This suggests that utilization of risk-adapted cancer treatments in Black children with ALL may be critical for OS (Dippenaar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chow et al (2010) discussed that although Black children have a 28% decreased risk for ALL (odds ratio = 0.72; confidence interval [0.65, 0.80]) compared with White and Hispanic children, there may be genetic (tumor and germline DNA) as well as environmental factors that increase their susceptibility to cancer. In addition, in epidemiologic studies of children with leukemia, unfavorable disease-specific characteristics were observed more in diverse racial/ethnic groups compared with White, non-Hispanics children (Aldrich et al, 2006;Njoku et al, 2013) and these unfavorable characteristics in the biology of the leukemia and/or genetic aberrations may contribute to disparities in OS for children with ALL (Linabery & Ross, 2008;Lohmueller et al, 2008;Reddy et al, 2018). This suggests that utilization of risk-adapted cancer treatments in Black children with ALL may be critical for OS (Dippenaar et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated that the survival rate of children with B-ALL was higher in European American children (EA) than in African American children (AA), which appeared to be due to the different canonical pathways affected in each case. Telomerase signaling is related to AA pathways, while chromosome aberrations in EA more frequently affect genes involved with homologous recombination [ 192 ]. This suggests that hTERT may have a different influence on B-ALL with regard to different populations; nonetheless, large-scale studies need to be done to verify this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the advent of microarray and next-generation sequencing (NGS) technologies, gene expression, DNA copy number, and mutation analyses has enabled the identification of many genetic abnormalities in tumor suppressors, cell cycle control genes, transcription factors and coactivators, and the genes involved in the development, proliferation, and signaling of B-cell lines. 1,3,6,7 More specifically, the use of NGS technologies in leukemia has changed the perspective of leukemia pathogenesis because it is possible to examine genetic abnormalities with massively parallel analysis and deep sequencing ability. 2,4,[7][8][9][10] In this study, mutation and expression analyses of genes considered to be genetic prognostic factors (associated with disease-free survival, overall survival time, risk of relapse, and treatment response) in independent studies were analyzed in our study group.…”
Section: Introductionmentioning
confidence: 99%